Philo of Alexandria: an annotated bibliography 2007-2016 with addenda for 1980-2006 - Runia, David T.; Alesso, Marta; Berthelot, Katell; Birnbaum, Ellen (Vigiliae Christianae, 2022)
"This volume is a further continuation of the annotated bibliographies on the writings and thought of the Jewish exegete and philosopher Philo of Alexandria, following those on the years 1937-1986 published in 1988, 1987-1996 published in 2000 and 1997-2012 published in 2012. Prepared in collaboration with the International Philo Bibliography Project, it contains a complete listing of all scholarly writings on Philo for the period 2007 to 2016. Part One lists texts, translations, commentaries etc. (75 items). Part Two contains critical studies (1143 items). In Part Three additional items up to 2006 are presented (27 items). In all cases a summary of the contents of the contribution is given. Six indices, including a detailed Index of subjects, complete the work"--